Economics Of Arecanut Cultivation In Kasargod District - Dineshkumar EV (Department of Agricultural Economics, College of Horticulture, 1994)
A study on the economics of arecanut cultivation in Kasaragod district was conducted during the period 1991-92 to evaluate the costs and returns, capital productivity, resource use efficiency of yielding plantation and the problems of arecanut cultivators. Three stage random sampling was adopted for the study and the data were collected from a sample of 144 cultivators by personal interview method. Total cost of cultivation for 11 years was estimated to be Rs.107133/- for the district, in terms of 1991-92 prices. The major item of expenditure was human labour constituting about 44.75 per cent of the total cost. Manures and fertilizers accounted for 25.92 per cent and cost on plant protection accounted for 9.27 per cent of the total cost for 11 years. The cost of production per quintal was estimated as Rs.1539/- for the district. Pay back period was found to be 8.91 years. Benefit cost ratio was calculated as 2.29. Net present worth was Rs.95506/- and internal rate of return was calculated to be 27.64 per cent. The factors manures and fertilizers and irrigation were found to have significant influence on the gross income obtained from an arecanut garden. The marginal value product of these inputs were found to be 1.262 and 7.07 respectively. High input costs, serious disease problems and difficulties associated with marketing were some of the general problems faced by the sample farmers.